Analisis Kemampuan Pemecahan Masalah Pada Materi Ekosistem Melalui Uji Instrumen Soal Uraian Terbuka - Feni Rianti; Yulianti Fitiyani; Atep Sujana; Encep Supriatna (Jurnal Penelitian Pendidikan IPA, 2026)
This study was conducted to analyze the problem-solving abilities of fifth-grade elementary school students through instrument testing. By using Polya's problem-solving indicators through open-ended Urian test instruments, students were guided to be able to explore their abilities in understanding, planning, implementing, and evaluating the results of their thinking in solving factual problems that occur in rice field and garden ecosystems. The method used in this study was quantitative descriptive with 27 fifth-grade students as subjects in an elementary school. The results of the analysis showed that the average problem-solving abilities of students were in the fairly good category, with an average overall score of 6.47 out of a maximum score of 10. The indicator with the highest achievement was the evaluation of results, while the indicator with the lowest achievement was the implementation of strategies. These results indicate that students' problem-solving abilities were still in the sufficient category, with a stronger tendency in the ability to evaluate results and understand problems than in planning problem-solving strategies.